P+d Plus Sliding Mode Control for Bilateral Teleoperation of a Mobile Robot - Salinas, Lucio Rafael (2018)
This paper proposes a control scheme based on combining a PD-like structure and a sliding mode control (SMC) applied to mobile robot bilateral teleoperation systems, in the face of asymmetric and time-varying delays. The proposal includes on the remote site both a P+d control and an SMC strategy in such a way that the advantages of both methods are exploited. The system stability is analyzed using Lyapunov-Krasovskii functionals and a delaydependent stability criteria is obtained using linear-matrix-inequalities (LMI). Finally, the teleoperation system is evaluated through human-in-the-loop experiments to confirm the theoretical results and test the robustness and stability of the proposed control scheme.